2023
DOI: 10.1038/s41612-023-00328-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Indian Ocean precipitation and its North Atlantic teleconnections during early winter

Abstract: The Tropical Western-Central Indian Ocean (WCIO) precipitation anomalies play an important role in modulating the anomalous climate conditions in the North Atlantic and European (NAE) region during the early boreal winter (November–December; ND) season. In this study, we analyzed the forcing mechanism and predictability for the early winter tropical WCIO precipitation anomalies and its teleconnections to the North Atlantic region. The two main forcing mechanisms emerging are the autumn Indian Ocean Dipole (IOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Whilst most of the literature has focused on the ENSO teleconnection to the North Atlantic in the late winter, recent studies have emphasised the intraseasonal variability of the teleconnection. In the early winter (November-December), the teleconnection is quite different from that in the late winter, with the associated sea-level pressure anomalies closely resembling the "East Atlantic" pattern (EA) rather than the NAO (Ayarzagüena et al, 2018;Geng et al, 2023;King et al, 2018;King et al, 2023;Moron & Gouirand, 2003), as also shown here in Figure 1a; in addition, some studies have highlighted the possible role of the tropical Indian Ocean in modifying the ENSO teleconnection to the North Atlantic in early winter (Abid et al, 2021(Abid et al, , 2023. Previous studies have demonstrated that free-running coupled climate models struggle to reproduce the early-season teleconnection to the North Atlantic (Ayarzagüena et al, 2018;Molteni, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…Whilst most of the literature has focused on the ENSO teleconnection to the North Atlantic in the late winter, recent studies have emphasised the intraseasonal variability of the teleconnection. In the early winter (November-December), the teleconnection is quite different from that in the late winter, with the associated sea-level pressure anomalies closely resembling the "East Atlantic" pattern (EA) rather than the NAO (Ayarzagüena et al, 2018;Geng et al, 2023;King et al, 2018;King et al, 2023;Moron & Gouirand, 2003), as also shown here in Figure 1a; in addition, some studies have highlighted the possible role of the tropical Indian Ocean in modifying the ENSO teleconnection to the North Atlantic in early winter (Abid et al, 2021(Abid et al, , 2023. Previous studies have demonstrated that free-running coupled climate models struggle to reproduce the early-season teleconnection to the North Atlantic (Ayarzagüena et al, 2018;Molteni, 2020).…”
Section: Introductionmentioning
confidence: 66%
“…The similarity between ENSO and IOPD is remarkable but not surprising. In a recent study, it was determined that ENSO's influence on boreal winter precipitation variability over some regions is primarily driven by atmospheric diabatic heating anomalies caused by ENSOdriven precipitation variability in the IO because of the strong coupling between IOPD and ENSO at a seasonal scale [17,50]. This is also true in SA, where the direct influence of contemporaneous ENSO forcing on monsoon precipitation becomes insignificant after controlling for the effects of IOPD and IOD (figure 2(b)).…”
Section: Resultsmentioning
confidence: 92%
“…Recent studies suggest that October IOD and contemporaneous ENSO can affect precipitation variability in the western Indian Ocean during early winter. 43 To understand this phenomenon more deeply, we analyze the association of bi-monthly IOPD with the October preconditioning of IOD and ENSO. In October, ENSO and IOD are strongly correlated (ERA5=0.67; MERRA2=0.62).…”
Section: Tropical and Extratropical Forcings In Seas5 And Spearmentioning
confidence: 99%
“…As the winter progresses, precipitation in the western Indian Ocean weakens (Figure S12), which correlates more with IOD. 43 Hence, IOD loses its influence over IOPD. On the other hand, ENSO strongly correlates with IOPD and eastern IO precipitation.…”
Section: Tropical and Extratropical Forcings In Seas5 And Spearmentioning
confidence: 99%